POLITIK HUKUM PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 1 TAHUN 2014 TENTANG PEMILIHAN GUBERNUR, BUPATI, DAN WALIKOTA - Muhammad Jeffry Rananda (Fiat Justisia: Jurnal Ilmu Hukum, 2015)
The formation of The government regulation a substitute for the law of the Republic of Indonesia Number 1 of 2014 on the Election of Governor, Regent, and Mayor? How does the process of formation of the government regulation a substitute for the law of the Republic of Indonesia Number 1 of 2014 on the Election of Governor, Regent, and Mayor studied in the political perspective of the law? A substitute for the law of regulation making process shows again that the law is a product of politics. The fact that a political institutions, that chooses to create the rule of law. Although empirically then the law will be reset the political institutions. A substitute for the law of regulation is a Ius Constitutum as regulations on local elections. However, A substitute for the act of regulation it will not be effective because it is only temporary. A substitute for the Law of regulation attestation required then it becomes a law or made the latest Law. Keywords: The government regulation a substitute for the Law, Legal Politics